Pengaruh Minat Pengunjung Penghuni Allogio Terhadap Padang Sinar Minang Allogio - Kevin; Sungoro, Messya Wijayanti; Cheung, Velicya Tarisha; Vinata, Jessica Natania; Waisa, Cheryl Jesslyn (Indra Institute Research & Publication, 2024)
Padang Sinar Minang Restaurant is a culinary business that is quite busy with visitors from the Alloggio cluster. Therefore, this research aims to investigate the influence of Alloggio visitors' interest in Padang Sinar Minang Alloggio Restaurant. To conduct this research, a qualitative research method was used with data collection through questionnaires. Data was collected from a research sample of 56 respondents living in the Alloggio cluster. The findings show that there is high buying interest from visitors to Alloggio residents towards the Padang Sinar Minang Alloggio Restaurant. This high buying interest is demonstrated by the frequency of consumer purchases, which at least once a week make a purchase at the Padang Sinar Minang Alloggio Restaurant. The main factors that influence this interest are price and taste (80.4%) where consumers think that the Padang cuisine offered has an appropriate price and taste. The higher the consumer's buying interest, the greater the interest of visitors from Alloggio residents to make purchasing decisions at the Padang Sinar Minang Alloggio Restaurant.